Enhancing Business Performance through Operational Planning, Exploratory Innovation and Manufacturing Strategy" - Muhammad Awais Bhatti; Khaled Mohammed Ahmed Alqasa (Decision Making: Applications in Management and Engineering, 2025)
Business performance is an integral factor because it helps organizations to achieve a competitive advantage. Therefore, the study aimed to test the influence of operational planning, exploratory innovation, exploitive innovation, environmental competitiveness, external environment, and manufacturing strategy on the business performance of manufacturing companies. For this purpose, a quantitative research approach and cross cross-sectional research design were employed to collect the data through a self-administered questionnaire. Collected data analyzed using SPSS and Smart-PLS 4. The PLS-SEM results shown that operational planning has a positive and significant influence on business performance. At the same time, innovation factors also have a significant positive influence on business performance. Environmental factors also have a significant positive influence on business performance. In addition, manufacturing strategy also has a positive and significant impact on business performance. The study with the specific results highlighted that organizations must invest in strengthening strategic planning, raising a culture of innovation, and continuously adapting to external environmental changes to improve overall business performance, which could lead to companies achieving a competitive advantage